An experimental study on a flow control device applicable in pressurized networks. (August 2019) - Rezazadeh, P.; Bijankhan, M.; Mahdavi Mazdeh, A.
Abstract: The flow control valve is able to deliver an almost constant discharge which is irrespective to the pressure fluctuations in a pressurized network. In this paper the design of a flow control device for incompressible flow is studied. The design criteria of the device are extended for wider discharge values up to Q = 0.6 l/s and differential pressure limits up to Δ p = 20 m . In this regard, experiments were performed on cylindrical orifice device to obtain the associated discharge formula, based on which, the initial valve design was obtained. Then, the performance of the flow control device was enhanced according to analyzing the experimental results of the initial design and modifying the float shape line. A step-by-step design framework was then proposed based on which the improved design criteria were achieved for the design discharges of Q = 0.4 l/s with 1≤Δ p ( m )≤7, Q = 0.6 l/s with 1≤Δ p ( m )≤7, and Q = 0.6 l/s with 2.6≤Δ p ( m )≤20. According to the experimental results, average discharge values of 0.391 l/s, 0.625 l/s, and 0.568 l/s, with the associated relative errors of 2.2%, 4.2%, and −5.3% were obtained in comparison with the design values. Graphical abstract: Image 1 Highlights: The design criteria for a Mechanical Choked Orifice Plate device is studied experimentally. A step-by-step experimental approach is proposed to extend the design parameters. The proposed control valve delivers an almost flow rate even if the differential pressure increases up to 20 m.